Social media communication : concepts, practices, data, law and ethics - Lipschultz, Jeremy Harris, 1958- (New York: Routledge, 2021)
"This updated third edition presents a wide-scale, interdisciplinary guide to social media. Examining platforms like Facebook, Instagram, LinkedIn, Snapchat, TikTok, Twitter and YouTube, the book analyzes social media's use in journalism, broadcasting, public relations, advertising and marketing. Lipschultz focuses on key concepts, best practices, data analyses, law and ethics - all promoting the critical thinking that is needed to use new, evolving and maturing networking tools effectively within social and mobile media spaces. Featuring historical markers and contemporary case studies, essays from some of the industry's leading social media innovators and a comprehensive glossary, this practical, multipurpose textbook gives readers the resources they will need to both evaluate and utilize current and future forms of social media communication. Among other changes, updates to the third edition include a deep dive into new approaches to analytics, as well as greater discussion of law and ethics in light of the Facebook Cambridge Analytica scandal, the roll-out of GDPR and new case law relating to social media. Social Media Communication is the perfect social media primer for students and professionals, and, with a dedicated teaching guide, ideal for instructors, too"--
Introduction to social media concepts -- CMC, diffusion and social theories -- Social media in journalism -- Social media in public relations -- Social media in advertising and marketing -- Social media metrics and analytics -- New and mobile media technologies, innovation and investment -- Big data and privacy -- Law and regulation -- Social media ethics -- Best practices in social media -- Future of social media and information literacy.
Includes bibliographical references and index.
Keywords: Social media; Social networks; Online social networks; Social media -- Law and legislation; Social media -- Moral and ethical aspects